Supercritical Algal Extracts: A Source of Biologically Active Compounds from Nature - Izabela Michalak; Agnieszka Dmytryk; Piotr P. Wieczorek; Edward Rój; Bogusława Łęska; Bogusława Górka; Beata Messyasz; Jacek Lipok; Marcin Mikulewicz; Radosław Wilk; Grzegorz Schroeder; Katarzyna Chojnacka (Journal of Chemistry)
The paper discusses the potential applicability of the process of supercritical fluid extraction (SFE) in the production of algal extracts with the consideration of the process conditions and yields. State of the art in the research on solvent-free isolation of biologically active compounds from the biomass of algae was presented. Various aspects related with the properties of useful compounds found in cells of microalgae and macroalgae were discussed, including their potential applications as the natural components of plant protection products (biostimulants and bioregulators), dietary feed and food supplements, and pharmaceuticals. Analytical methods of determination of the natural compounds derived from algae were discussed. Algal extracts produced by SFE process enable obtaining a solvent-free concentrate of biologically active compounds; however, detailed economic analysis, as well as elaboration of products standardization procedures, is required in order to implement the products in the market.